Family-friendly work practices in Britain: availability and perceived accessibility - Budd, John W.; Mumford, Karen (Bonn, 2005)
"Using linked data for British workplaces and employees we find a low base rate of workplace-level availability for five family-friendly work practices – parental leave, paid leave, job sharing, subsidized child care, and working at home – and a substantially lower rate of individual-level perceived accessibility. Our results demonstrate that statistics on workplace availability drastically overstate the extent to which employees perceive that family-friendly are accessible to them personally. British workplaces appear to be responding slowly and perhaps disingenuously to pressures to enhance family-friendly work practices."